Pengaruh Kompres Serai Hangat terhadap Intensitas Nyeri Arthrtitis Rheumatoid pada Lanjut Usia di Panti Sosial Tresna Werdha Budi Luhur - Nurfitriani Nurfitriani; Tina Yuli Fatmawati (Universitas Baiturrahim, 2020)
Rheumatoid arthritis or often called rheumatism is a disorder that continues to undermine health and destroy the quality of human life, several types of rheumatic disorders have been identified earlier so that the number of sufferers will increase as more people develop rheumatism, so the need for treatment will increase as well. Data obtained at Tresna Werdha Social Home, out of 70 elderly people, 43 of them suffered from rheumatoid arthritis. The purpose of this study was to determine the effect of Warm Lemongrass Compress Against Pain Intensity in Rheumatoid Arthritis in Elderly People at Tresna Werdha Social Home Budi Luhur Jambi. The research design used was a Pre-Experiment design with One Group Pre-Post Test Design. The study was conducted at the Budi Luhur Nursing Home in Jambi. The sampling method was carried out using purposive sampling, with 15 respondents consisting of the Serai compress. Analysis of the data will be used univariate analysis and bivariate analysis with the t-test Dependent. The results were obtained. by pain intensity in elderly Rheumatoid Arthrtitis before the average treatment 6.90 and after the pain is reduced to an average of 4.13. There is an effect of giving warm lemongrass compresses on decreasing the intensity of Rheumatoid Arthritis pain in the elderly at Tresna Werdha Social Home in Jambi City with p-value = 0,000. It is recommended to the room nurse or the person in charge of the room to be able to try to implement or demonstrate of warm lemongrass compresses so as to reduce the intensity of pain in the elderly.